Overview of Work-Life Balance on Married Female Nurses at Cut Meutia General Hospital - Dewi, Rahmia; Livia Salvawirza (HM Publisher, 2022)
This study aims to describe the description of work-life balance in married female nurses at Cut Meutia General Hospital. This research was conducted at Cut Meutia General Hospital, North Aceh. The method in this research is descriptive and quantitative. The number of participants in the study consisted of 76 married nurses. This study uses the work-life balance dimension, which consists of four dimensions, namely, work interference with personal life (WIPL), personal life interference with work (PLIW), personal life enhancement of work (PLEW), work enhancement of personal life (WEPL). The technique used in this research is non-probability sampling with purposive sampling. The data collected in this study used a Likert scale, namely the work-life balance scale, which amounted to 22 items. Data analysis shows that the overall work-life balance of married female nurses at Cut Meutia General Hospital is in high categorization, namely 53.9%. The results of this study have a positive effect on work in personal life and have a positive effect that is formed from the realm of personal life to the respondent's work. In conclusion, married female nurses are able to balance their personal life and work (work-life balance). The PLIW dimension is the lowest at 53.9%. This shows that a person's personal life is very influential